The institutionalization of the Handcrafts Fair of Beira Mar, Fortaleza, Ceará, Brazil (Gestão & Regionalidade, 2016)
Part of Ceará's culture for over thirty years, the Craft Fair of Beira Mar has increasingly emerged in national and international levels, having gone through changes of several orders. Thus, this research aims to analyze the process of institutionalization of the Craft Fair of Beira Mar in Fortaleza, Ceará, Brazil, using the model of institutionalization of Tolbert and Zucker (1998) process, which consists of three phases: habitualization, objectification and sedimentation. This is a qualitative, documentary and field research, with semi-structured interviews being held with 29 stallholders and analyzed through content analysis technique. The results showed that the main factor that motivated the emergence of the fair was of economic nature, since it sought for a way to survive, with the stallholders being the main actors in this process. The fair is in the stage of sedimentation and the normative isomorphism predominates, followed by coercive isomorphism.